The food exorcism - Niola, Marino (E|C, 2020)
Diet is not simply a way of eating but, rather, an art of living. Or, as we would say today, a lifestyle. The etymology of the Greek word “diaita” - from which our "diet" - derives, according to some linguists, from a root *djao, which has to do with living. And in any case it designates, in general, a rule of conduct that does not necessarily have food as its object, but serves to give measure to many forms of behavior.